The distribution of Corbicula fluminea (Muller, 1774) and its outer shell colour in Sabah and Sarawak. Issue 1 (May 2021) - Aweng, E R; Arham Muchtar, A B; Salam, M A; Sharifah Aisyah, S O; Azlan, A; Zulhazman, H; Mohammad Amizi, A; Zul Ariff, A L
Abstract: Corbicula fluminea is one of the freshwater bivalves, which is small in size and lives in the river or at the bottom of the lake all over Malaysia including Sabah and Sarawak. Corbicula fluminea comes in different outer shell colour for different sites. The differences in outer shell colour are believed to be due to substrates composition, and land uses. Thus, to determine the distribution of Corbicula fluminea in Sabah and Sarawak and to determine the influence of river substrates and land uses on the outer shell colour of Corbicula fluminea, a survey was conducted in the selected area involving Sabah and Sarawak. The method utilized was by obtaining information from the villagers through informal conversational interview, observations, and followed by collecting the samples at the river using a special tool. The coordinate of each place where the sample was taken was recorded using the Garmin model GPSmap 62. Meanwhile, the digital calliper was used to measure shell height (H) and length (L). Statistical analysis of the chi-square test has been used to determine the relationship between the considered categorical variables in this study. Results indicate that the state of Sarawak has an irrigation canal that provides irrigation to the paddy field and one river, namely Sarawak Kanan River, which contains C. fluminea . As for Sabah, C. fluminea was found in 2 irrigation canals that also provide irrigation to paddy fields and 2 rivers, namely Tempasok River in Kota Belud and Kinarut River in Papar. Meanwhile, from the chi-square test result clearly shows that the outer shell colour of the C. fluminea depends on the type of substrate and landuse but not influenced by the location neither by zone nor the area such as urban, suburban or rural at the significant level of 0.05. This data is expected to be used by the authorities responsible for finding the conservation and restoration methods to ensure that C. fluminea does not disappear from the state of Sabah and Sarawak. This study could also help to ensure that the source of income for traditional fishermen who depend on C. fluminea is not affected.